ETHICAL BEHAVIOR OF ACCOUNTANTS IN DEALING WITH FINANCIAL STATEMENT FINDINGS: BUSINESS PROJECTIONS FACING ARTIFICIAL INTELLIGENCE - Arum Yulistiyaningsih; Handhika Dharmawan; Dody Waringgi; Bintoro Ariyanto (Economos : Jurnal Ekonomi dan Bisnis, 2025)
HR management is responsible for creating and maintaining an organizational culture that supports integrity and ethical behavior. When an organization has a culture that emphasizes transparency, accountability, and ethics, the pressure on accountants to manipulate financial reports can be minimized. This research aims to explore the background, influencing factors, and strategies used by accountants in dealing with pressures related to post-pandemic financial reporting with artificial intelligence-based business projections. The research method used uses a quantitative and qualitative approach. The research results reveal that the Pearson correlation coefficient between experience and ethical decisions is -0.038, which indicates there is almost no linear relationship between the two. This very weak correlation suggests that a person's work experience does not have a significant influence on their ability to make ethical decisions. The results of the t test between ethical decisions and external pressure show a t value of -2.33 with a p-value of 0.018. Since the p-value is lower than the 0.05 significance level, this indicates that external pressure has a significant influence on the ethical decisions taken. The strategies that can be implemented are based on artificial intelligence, by building ethics-based governance, responsible digital transformation, increasing human resource capabilities, business diversification to reduce risk, optimizing data-based decisions.